Topical adjunctive treatment with flagellin augments pulmonary neutrophil responses and reduces bacterial dissemination in multidrug-resistant K. pneumoniae infection - van Linge, Christine C. A.; Kullberg, Robert F.J.; Chouchane, Osoul; Roelofs, Joris J. T. H.; Goessens, Wil H. F.; van ‘t Veer, Cornelis; Sirard, Jean-Claude; de Vos, Alex F.; van der Poll, Tom (Frontiers in Immunology, 2024)
Objective Antimicrobial resistance is an emerging problem and multi-drug resistant (MDR) Klebsiella pneumoniae (K. pneumoniae) represents an enormous risk of failing therapy in hospital-acquired pneumonia. The current study aimed to determine the immunomodulatory effect of topical flagellin in addition to antibiotic treatment during respiratory infection evoked by hypervirulent antibiotic-susceptible and antibiotic-resistant K. pneumoniae in mice. Methods C57BL6 mice were inoculated intranasally with hypervirulent K. pneumoniae (K2:O1) which was either antibiotic-susceptible or multi-drug resistant. Six hours after infection, mice were treated with antibiotics intraperitoneally and flagellin or vehicle intranasally. Mice were sacrificed 24 hours after infection. Samples were analyzed for bacterial loads and for inflammatory and coagulation markers. Results Flagellin therapy induced neutrophil influx in the lung during antibiotic-treated pneumonia evoked by either antibiotic-susceptible or -resistant K. pneumoniae. The pulmonary neutrophil response was matched by elevated levels of neutrophil-attracting chemokines, neutrophil degranulation products, and local coagulation activation. The combined therapy of effective antibiotics and flagellin did not impact K. pneumoniae outgrowth in the lung, but decreased bacterial counts in distant organs. Neutrophil depletion abrogated the flagellin-mediated effect on bacterial dissemination and local coagulation responses. Conclusion Topical flagellin administration as an adjunctive to antibiotic treatment augments neutrophil responses during pneumonia evoked by MDR-K. pneumoniae, thereby reducing bacterial dissemination to distant organs.